De Apographo Quodarn Matritenst * Moa íówoq FIcpi Fuvctuccíwv flaOéSv - Floristán Imizcoz, José M. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
The arranging of the personal archives of Infante Gabriel de Borbón has provided us with a new manuscript of Mosquion’s Gynaecology. Mosquion is known since the Renaissance as a Greek physician of the late period, until V. Rosé ir’ 1881 drew our attention to the true nature of bis work as a translation of a latin original. The author of this essay takes as starting po¡nt a photocopy of the aforementioned work -—the original being unluekily lost nowadays–—, describes the manuscript. examines its relationship with the most important codices of the Latin original and studies its most remarkable linguistic léatures, which clearly confirm V. Rose´s conclusions.